Humanitarian Projects and Research in the Field of Formation, Development and Integration of the Socio-Cultural Information Space of Ukraine in the Activities of the V. I. Vernadsky National Library of Ukraine - Hryshchenko Yulia (Наукові праці Національної бібліотеки України імені В.І. Вернадського, 2024)

(untitled)
An important component of historical research into the history of national and regional aspects of culture is an understanding of the socio-cultural space of Ukraine in its diversity. Library resources play a significant role in the implementation of the nationwide project of forming the appropriate information field. In this context, the activities of the National Library of Ukrainen amed after V. I. Vernadsky (NBUV) and a number of projects implemented with the participation of the Library, which systematically form electronic resources, which provide a scientific vision of national and regional specifics, ways of integrating information and serve as a source basis for studying the history and present-day development of cultural processes, explore various aspects of the development of socio-cultural trends, are of particular interest. The purpose of the study is a general overview of the scientific and research projects of the National Library of Ukraine in the field of formation and development of national resources of historical and cultural development of Ukraine, developed by specialists of the National Library of Ukraine, the development of universal in content national collections of historical and cultural heritage, the formation on their basis of large-scale electronic digital resources that laythe foundations for the study of topical issues of the completeness and representativeness of the national cultural space. The importance of inter-institutional projects in the implementation of the tasks set is emphasized. The works of librarians aimed at the theoretical understanding of the information aspect of the development of the socio-cultural space of Ukraine are summarized. The main directions of the relevant developments of the National Library of Ukraine are determined: first, studies that reveal the activities of the scientific divisions of the Library that work directly with the funds as historical and cultural heritage and scientific resources; secondly, studies related to library digital projects; and, thirdly, a cycle of research related to the issues of forming a holistic socio-cultural space of Ukraine as a component of consolidation national strategies and information synthesis of the Ukrainian national space. This allowed us to reveal the profound contribution of the scientists of the National Library of Ukraine to the formation of a holistic socio-cultural information development of Ukraine, which today is of great importance in the conditions of information cooperation and information confrontations of wartime, providing an opportunity to defend Ukraine’s right to independence and national development in the modern globalized world.